Educational Flagships as Brokers in International Policy Transfer: Learning from the Experience of Kazakhstan. Issue 4 (2nd October 2018) - Kuzhabekova, Aliya; Soltanbekova, Arailym; Almukhambetova, Ainur
Abstract : In this article we analyze a recent development in educational reform in Kazakhstan, which presents interest to researchers of policy transfer/borrowing. We argue not only that international policy transfer has become the main approach to educational reform, but also that the approach has been institutionalized by the establishment of a specialized organizational structure, represented by a system of flagship institutions at different levels of education, which were assigned the role of identifying, adapting, testing, and disseminating the best international practices. Reconsidering policy transfer at the organizational level as knowledge transfer, we use ideas from interorganizational learning theory to interpret the narrative data from interviews with the employees of the flagships and of the educational organizations, to which they disseminate best practices. In doing so, we attempt to explore the factors which may influence the success of institutionalized policy transfer from brokers to downstream adopters of innovation.